Effects of Emotional States on Reproducibilities of Rest Position, Social and Spontaneous Smiles, and Speech - Işıl Bulut; İlke Şahin; Furkan Dindaroğlu (Turkish Journal of Orthodontics)
Objective: To evaluate the effect of emotional states on reproducibilities of rest position, social and spontaneous smiles, and speech. Methods: A total of 30 individuals aged 18-22 years were included (mean age; 19.03 years ±1.03). Three emotional states were determined: amusing, sadness, and neutral. The participants watched three different videos in 3 sessions on the same day. After each video, the participants completed a questionnaire to assess their mood. The rest position, social and spontaneous smiles, and speech recordings were gathered from the participants using videographic method. Measurements were made for each function. The Friedman test, One-Way ANOVA, Kruskal-Wallis test was performed for statistical evaluations, and intra-observer correlation coefficients and Bland-Altman Limits of Agreement were calculated. Results: In spontaneous smiles, there were significant differences between amusing and sadness in the smile height (p=0.020); amusing and sadness in the lower lip thickness (p=0.029). In social smiles there was a significant difference between amusing and sadness in the maxillary incisor display (p=0.006). There were no statistically significant differences in the rest position, but clinically significant differences were observed in some participants. In speech, a significant difference was found between amusing and sadness in the distance between the upper lip and subnasal (p=0.035). Conclusion: The reproducibility of social and spontaneous smiles was influenced by various emotional states. However, the rest position exhibits higher reproducibility than social and spontaneous smiles in all emotional states.